Matouš Konečný a jeho podíl na výchově a vzdělávání bratrských duchovních na počátku 17. století - Jiří Just (Theatrum Historiae)
Matouš Konečný, the bishop of the Bohemian Brethren in Mladá Boleslav between 1609‒1622, was responsible also for the education of deacons and priests of this protestant confession. The realization of this mission made him possible his contacts with Matthias Martini, the rector of the Gymnasium illustre at Bremen. In the Book about the duty of Christians, printed 1612 and 1616, presented Konečný one‘s own ideas about the Christian education.